2022
DOI: 10.1155/2022/3390831
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Neutrophil to Lymphocyte Ratio in Guillain Barré Syndrome: A Systematic Review and Meta-Analysis

Abstract: In this study, we conducted a systematic review and meta-analysis regarding the role of the neutrophil to lymphocyte ratio (NLR) in Guillain Barré syndrome (GBS). The most recent update to the search was on July 18, 2022, through the databases of Web of Science, PubMed, Embase, and Scopus. The Newcastle-Ottawa scale was used for quality assessment of included studies. Finally, 14 studies were included in the review, and among them, ten studies were included in the meta-analysis. Our results showed that NLR lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Moreover, assessing ECG parameters in conduction system disease in victims of COVID-19, ST-T changes, fragmented QRS, axis deviation, presence of S1Q3T3, and poor R wave progression were significantly related to conduction disease in victims of COVID-19. possible suggestive of new-onset myocardial infarctions during the infection, increasing the risk of mortality (38)(39)(40). This may indicate that COVID-19 adversely affects cardiac myocardial tissue more than how it was taken for granted.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, assessing ECG parameters in conduction system disease in victims of COVID-19, ST-T changes, fragmented QRS, axis deviation, presence of S1Q3T3, and poor R wave progression were significantly related to conduction disease in victims of COVID-19. possible suggestive of new-onset myocardial infarctions during the infection, increasing the risk of mortality (38)(39)(40). This may indicate that COVID-19 adversely affects cardiac myocardial tissue more than how it was taken for granted.…”
Section: Discussionmentioning
confidence: 99%
“…In Alzheimer's disease (AD) and Parkinson's disease (PD), typical neurodegenerative diseases, persistent neuroinflammation by microglia is involved in the onset and worsening of these conditions. Furthermore, inflammation is involved in neurological diseases such as epilepsy and Guillain-Barré syndrome [20,21]. Therefore, suppressing neuroinflammation might ameliorate symptoms of neurodegenerative diseases [19].…”
Section: Epilepsy Tand and Neurodegeneration In Tsc Model Micementioning
confidence: 99%
“…It has been shown that inflammatory factors apart from cellular and humoral immunity play a role in the pathogenesis of GBS [10]. Numerous hematology indicators, including neutrophil-to-lymphocyte ratio (NLR), platelet−lymphocyte ratio (PLR), C-reactive protein, systemic inflammation response index (SIRI) and systemic immune-inflammation index (SII) in GBS patients have been explored in several studies before [11][12][13][14][15], but these parameters have not been studied in inflammatory neuropathies clinical subgroups, and the correlation between these parameters and disease severity needs further research. Additionally, uric acid (UA) is a strong natural scavenger of reactive oxygen and nitrogen species.…”
Section: Introductionmentioning
confidence: 99%